Microscopic, submicroscopic characterization of pro- and anti-inflammatory cell phenotypes of the lungs in conditions of experimental allergic inflammation - S. S. Popko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The aim is to study the microscopic and submicroscopic characteristics of pro- and anti-inflammatory cell phenotypes of the lungs under conditions of experimental allergic inflammation.